Contribution to the knowledge of the genus Phaneroptera (Tettigoniidae: Phaneropterinae) with a new record from Tamilnadu, India - Divya, Govindaraj; Senthilkumar, Natchiappan (Zootaxa, 2020)
The genus Phaneroptera (Tettigoniidae: Orthoptera) has been represented in India by four species. One additional species of Phaneroptera is described based on the variation in lateral lobe of pronotum, cerci of male and modifications of the subgenital plate. The morphometrics of the species are presented, which include P. spinosa, P. gracilis, P. falcata, P. myllocerca and Phaneroptera rentzi sp. nov. Key to the species of the genus Phaneroptera in India is provided.